Container-based sanitation in urban Haiti: how can it improve human rights as a component of citywide inclusive sanitation?. Issue 1 (15th March 2022) - VanRiper, Froggi; Russel, Kory C.; Tillias, Daniel; Tilt, Jenna; Laporte, Jessica
Abstract: Health, sanitation, and livelihoods are interrelated human rights and essential components of community wellbeing. Despite the United Nations recognizing the human right to sanitation, one-third of the world's population lack access to improved sanitation. Furthermore, in many low- and middle-income countries, urban latrines are excavated manually without physical or regulatory protections. Container-based sanitation (CBS) has promise as a component of Citywide Inclusive Sanitation (CWIS) in densely populated, low-resource environments. Before investing in CBS, however, governments and funders require evidence of user acceptance, public demand, and labor aspects of service delivery. To provide this evidence base, we completed 633 interviews with active and former users of EkoLakay, a CBS service in Cap Haïtien, Haiti, creating a profile of the user base and their motivations for subscribing. We also compiled and analyzed secondary data to determine the impacts of widespread CBS expansion in northern Haiti. Results reveal that CBS presently serves a geographical subset of Haiti's most resource-insecure residents, and that CBS significantly reduces handling of untreated excreta in Haiti's Nord Department, while doubling livelihood opportunities through safe and dignified jobs. Given its cost-effectiveness, this provides an opportunity to achieve widespread sanitation coverage by integrating and cross-subsidizing CBS within a CWIS strategy. HIGHLIGHTS: First systematic study of CBS's impact on vulnerable households. Haiti's sanitation system leaves 19% of urban households without improved sanitation access. Haitian CBS users had above-average rates of open defecation and limited sanitation pre-CBS. CBS could help urban sanitation systems in LMICs achieve SDG 6. CBS can replace 1 M hours of unsafe excreta-handling labor with 500+ safer jobs in northern Haiti. Graphical Abstract